2021
DOI: 10.46754/jssm.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Saltwater Intrusion on Paddy Growth in Kuala Kedah, Malaysia

Abstract: Many initiatives and strategies have been implemented by the government to improve the paddy sector. A local authority, known as the Muda Agricultural Development Authority (MADA), was established in 1970 to provide assistance to farmers in Kedah. Kamaruddin et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This is due to sea water's existence in the paddy plot caused by sea water intrusion especially during high tide phenomenon and heavy rain events. A previous study by Ercan, Fauzi, & Kavvas, (2013); Reddy et al, (2017);Samsuddin Sah et al, (2020) found that the salinity concentration of more than 1100 ppm will directly stunt the paddy growth and in turn lead to a reduction in rice yields at affected areas. This also supported by Fogliatto, Serra, Patrucco, Milan and Vidotto, (2019) ;Khanom, (2016) where the growth reduction due to root damage, ion toxicity, lessened nutrient and water uptake, and inhibition of photosynthesis will lead to the decrement of yields Hence, this study was conducted to assess the level of salinity in two different seasons and describe the level of salinity concentration using salinity variability map using Inverse Distance Weighted (IDW) interpolation methods that are available in ArcGIS software for both the season.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to sea water's existence in the paddy plot caused by sea water intrusion especially during high tide phenomenon and heavy rain events. A previous study by Ercan, Fauzi, & Kavvas, (2013); Reddy et al, (2017);Samsuddin Sah et al, (2020) found that the salinity concentration of more than 1100 ppm will directly stunt the paddy growth and in turn lead to a reduction in rice yields at affected areas. This also supported by Fogliatto, Serra, Patrucco, Milan and Vidotto, (2019) ;Khanom, (2016) where the growth reduction due to root damage, ion toxicity, lessened nutrient and water uptake, and inhibition of photosynthesis will lead to the decrement of yields Hence, this study was conducted to assess the level of salinity in two different seasons and describe the level of salinity concentration using salinity variability map using Inverse Distance Weighted (IDW) interpolation methods that are available in ArcGIS software for both the season.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is a measure of the dissolved salts in the water. Salinity is usually highest during periods of low flows and increases as water levels decrease (Hoang, Williams, Khanna, Dale, & Mundree, 2014;Mccaffrey, 1997;Samsuddin Sah, Abdul Maulud, Sharil, A. Karim, & Abdul Nahar, 2020). Sources of salinity include urban and rural run-off containing salt, fertilizers and organic matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation